2016
DOI: 10.1177/2050303216676523
|View full text |Cite
|
Sign up to set email alerts
|

Love in the Middle East: The contradictions of romance in the Facebook World

Abstract: Romantic love is a social fact in the Muslim world. It is also a gender politics impinging on religious and patriarchal understandings of female modesty and agency. This paper analyzes the rise of love as a basis of mate selection in a number of Muslim-majority countries: Algeria, Egypt, Iran, Pakistan, Palestine, Tunisia, and Turkey where we have conducted Web-based anonymous surveys of Facebook users. Young people increasingly want love in their married lives, but they and the communities in which they live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…population that uses FB-known as the penetration rate-varies by country. Algeria and Egypt have the lowest penetration rates while Turkey, Palestine, and Tunisia have much greater rates (see Friedland et. al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…population that uses FB-known as the penetration rate-varies by country. Algeria and Egypt have the lowest penetration rates while Turkey, Palestine, and Tunisia have much greater rates (see Friedland et. al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“… 15 In an earlier study, we also found that support for the hijab has absolutely no relationship to the pursuit of love as a criterion of spousal choice (Friedland et al., 2016). …”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Afary and Friedland's article, "Critical Theory, Authoritarianism, and the Politics of Lipstick: From Weimar Republic to the Contemporary Middle East," draws upon studies on authoritarianism pioneered by Fromm in 1929 and Adorno in 1950, with an emphasis on questions concerning the link between the decline in patriarchal authority, the rise of feminism, and masculine control over women's bodies. Basing their work on Facebook surveys that they conducted between 2012 and 2013 in seven Muslim majority countries and in the diaspora, Friedland, Afary, Gardinali et al, (2016) compiled over 19,000 responses to questions concerning "family, sex, religion, and democracy." Like Fromm's 1929 survey, they accounted for religious affiliation and class in order to explore links between monist absolutism and authoritarianism with views on makeup and women's empowerment.…”
Section: University Of Toronto Canadamentioning
confidence: 99%